Titanium alloy bar with high fatigue performance and preparation method thereof

By depositing a TiAl alloy coating on the surface of titanium alloy bars and performing low-temperature ion nitriding treatment to form a composite surface modification layer, the wear problem of titanium alloy bars under frictional contact and alternating fatigue loads is solved, and the high fatigue performance and wear resistance are improved.

CN120967303AActive Publication Date: 2025-11-18SHAANXI ZHONGJING NON-FERROUS METAL CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202511492051.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-20
Publication Date
2025-11-18
Estimated Expiration
2045-10-20

AI Technical Summary

Technical Problem

Titanium alloy bars are prone to wear under frictional contact and alternating fatigue loads. Conventional surface treatments improve wear resistance but impair fatigue performance.

Method used

A TiAl alloy coating is deposited on the surface of a titanium alloy rod and subjected to low-temperature ion nitriding to form a nitriding layer. A composite surface modification layer is formed between the TiCuAl or TiNiAl coating and the substrate, including low-temperature nitriding and polishing.

Benefits of technology

It significantly improves the fatigue resistance of titanium alloy bars, enhances surface hardness and wear resistance, while maintaining the microstructure and performance stability of the matrix.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a high-fatigue-performance titanium alloy bar and a preparation method thereof, and relates to the technical field of titanium alloy surface treatment.The preparation method comprises the following steps that a titanium alloy bar is taken as a base body, and a TiAl alloy coating is deposited on the surface of the titanium alloy bar; and then low-temperature ion nitriding is conducted, a nitriding layer is formed, and the high-fatigue-performance titanium alloy bar is obtained. Through surface TiAl alloying and low-temperature ion nitriding, a composite surface modification layer is formed on the surface of a titanium alloy matrix, Cu, Ni and Al contribute to refinement of nitride grains, sufficient Ti elements are provided for subsequent nitriding, a nitriding layer which is firmly combined with the matrix, high in hardness and high in abrasion resistance is formed, meanwhile, residual compressive stress is introduced to the surface, and therefore the corrosion resistance of the titanium alloy matrix is improved. Therefore, the anti-fatigue performance of the titanium alloy bar is remarkably improved, and the microstructure and performance characteristics of a titanium alloy matrix are kept.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to the technical field of titanium alloy surface treatment, and particularly relates to a titanium alloy rod with high fatigue performance and a preparation method thereof. BACKGROUND

[0002] In the field with extreme performance requirements, the titanium alloy rod with surface plating cannot be replaced. The plating coating types include wear-resistant plating, fretting fatigue-resistant plating, oxidation-resistant plating, corrosion-resistant plating, dry film lubricating coating and the like. Some titanium alloy parts often bear frictional contact and alternating fatigue load during service. However, the titanium alloy has low hardness and poor wear resistance, and is easy to be worn when frictionally contacting with the titanium alloy or other materials, which greatly limits the engineering application of the titanium alloy. While the conventional surface treatment such as electroplating, thermal spraying and vapor deposition can improve the wear resistance of the titanium alloy, the fatigue performance of the titanium alloy is often severely damaged. Therefore, the titanium alloy rod with high fatigue performance and the preparation method thereof are provided. SUMMARY

[0003] The application aims to provide a titanium alloy rod with high fatigue performance and a preparation method thereof to solve the problems in the background.

[0004] In order to solve the above technical problems, the application provides the following technical scheme: a preparation method of a titanium alloy rod with high fatigue performance, comprising the following processes: The titanium alloy rod is taken as a substrate, a TiAl alloy coating is deposited on the surface of the substrate, low-temperature ion nitriding is performed, a nitriding layer is formed, and the titanium alloy rod with high fatigue performance is obtained.

[0005] Further, the titanium alloy substrate comprises the following components: iron: ≤0.30%, carbon: ≤0.08%, nitrogen: ≤0.03%, oxygen: ≤0.25%, hydrogen: <0.005%, and the balance is titanium and other alloy elements.

[0006] Further, the titanium alloy substrate is one of TA2, TC4, Ti-6Al-4V, GR2, GR4 and TA15.

[0007] Further, the titanium alloy substrate comprises the following components: aluminum (Al): 4.5-5.5%, molybdenum (Mo): 4.0-5.0%, vanadium (V): 4.5-5.5%, chromium (Cr): 3.0-4.0%, zirconium (Zr): 3.5-4.5%, tantalum (Ta) or palladium (Pd): 0.5-1.0%, iron (Fe): ≤0.25%, carbon (C): ≤0.08%, nitrogen (N): ≤0.03%, oxygen (O): ≤0.10%, hydrogen (H): <0.005%, and the balance is titanium (Ti).

[0008] The substrate is cleaned and surface-activated to remove the oxide layer and contaminants.

[0009] In the above technical solution, the titanium alloy substrate includes a basic high-strength and high-toughness component: Ti-Al-Mo-V-Cr-Zr system, and the performance is achieved through the composite addition of multiple groups of beta-stable elements and aging strengthening; and contains a high fatigue resistance component: on the basis, the impurity content of Fe, O and the like is reduced, and beneficial elements such as Mo and Zr are preferentially selected to ensure the purity of the alloy and reduce the fatigue crack initiation point from the source.

[0010] Aluminum (Al) is the main alpha phase stabilizing element and solid solution strengthening element. It improves the strength, elastic modulus and thermal strength of the alloy, but excessive amount will form a brittle phase, reducing toughness and thermal stability. Molybdenum (Mo), Vanadium (V), and Chromium (Cr) are beta phase stabilizing elements, as core elements, they can greatly improve the hardenability, ensuring that the entire cross-section of the material can obtain uniform beta phase structure during heat treatment; play a solid solution strengthening role, strengthen the beta phase matrix; and in subsequent aging treatment, fine alpha phase is precipitated from the metastable beta phase, realizing high strength of the alloy. Zirconium (Zr) is a neutral element, which has a large solid solubility in both alpha-Ti and beta-Ti, can significantly enhance the solid solution strengthening effect without significantly changing the phase ratio; at the same time, it can improve the strength and toughness, and improve the hot working performance. Palladium (Pd) or Tantalum (Ta) is a noble metal element, which can greatly improve the corrosion resistance of the alloy, and has excellent crack corrosion resistance in non-oxidizing reducing acid and chloride environment. Iron (Fe), oxygen (O), and hydrogen (H) are impurity elements, which need to be strictly controlled at a low level to prevent their negative impact on plasticity, toughness and thermal stability.

[0011] Further, the titanium alloy substrate is prepared by the following process: The titanium sponge and alloying elements are mixed, melted, and cast into ingots; then, the ingots are sequentially subjected to forging, rolling, heat treatment, machining, surface treatment, non-destructive testing and physical and chemical testing, marking, packaging and storage.

[0012] Further, the titanium sponge is grade 0 titanium sponge, and the alloying elements are added in the form of aluminum particles, Al-Mo intermediate alloy, Al-V intermediate alloy, Al-Cr intermediate alloy, pure Zr, and pure Ta / Pd particles.

[0013] Further, the melting adopts vacuum consumable arc melting, low-current arc starting, first melting with a melting current of 8000-10000 A, secondary VAR melting with a current of 10000-12000 A, and third melting with a current of 12000-15000 A, with a vacuum degree of <5×10 - 2 Pa.

[0014] Further, the forging includes the following processes: blooming: temperature 1050-1150℃, deformation per heating 20-40%, total deformation >60%, final forging temperature ≥950℃; intermediate forging: temperature 900-950℃, deformation per heating 30-50%, total deformation 50-70%, final forging temperature ≥850℃; final forging: temperature 800-820℃, deformation per heating 15-30%, total deformation 40-60%, final forging temperature ≥780℃, air or water cooling.

[0015] Further, in the rolling process, the heating temperature is 800-850℃, the final rolling temperature is >800℃, the deformation per pass is 10-20%, the total deformation is 70-90%, and the final rolling temperature is ≥780℃; air cooling.

[0016] Further, the heat treatment adopts annealing or solid solution + aging, solid solution treatment: temperature 870-890℃, holding time 1 hour + 1 hour per 25mm section, water quenching; aging treatment: temperature 500-580℃, holding time 4-8 hours, air cooling; annealing: temperature 800-820℃, holding time 1-2 hours, air cooling.

[0017] Further, the surface treatment includes pickling and sandblasting / shot blasting. Pickling uses HF-HNO3 mixed acid solution to remove surface oxide layer (α contamination layer) and embedded iron contamination. Sandblasting / shot blasting is used to improve the surface state or introduce beneficial residual compressive stress to improve fatigue strength.

[0018] In the HF-HNO3 mixed acid solution, HF:HNO3:H2O=1:3:(6-10), pickling temperature 40-50℃, time 5-15min; Sandblasting uses 100-150 mesh alumina sand or glass beads, pressure 0.3-0.5MPa; In the shot blasting process, the intensity is 0.15-0.25mmA, the coverage is ≥100%, and the shot is cast steel shot, ceramic shot or glass shot.

[0019] Further, the TiAl alloy coating is obtained by direct current magnetron sputtering deposition, The process parameters of magnetron sputtering are: power 80-120W, working pressure 0.4-0.8Pa (3-6mTorr), target-substrate distance 100-120mm, and substrate rotation speed 10-20rpm.

[0020] Further, the target material used for preparing the TiAl alloy coating is TiAl alloy target material, TiCuAl alloy target material or TiNiAl alloy target material.

[0021] Further, the TiCuAl alloy target material comprises the following components: Ti: 60-70%, Cu: 20-30%, and Al: 5-10% by mass, and a TiCuAl alloy coating is deposited.

[0022] Further, the TiNiAl alloy target material comprises the following components: Ti: 60-70%, Ni: 20-30%, and Al: 5-10% by mass, and a TiNiAl alloy coating is deposited.

[0023] Further, the TiAl alloy coating has a thickness of 1-3 μm.

[0024] Further, the low-temperature ion nitriding process is as follows: The titanium alloy with the TiAl alloy coating deposited thereon is placed in a vacuum chamber of an ion nitriding furnace, and after vacuumizing, a mixed gas of nitrogen (N2) and argon (Ar) is introduced, the gas pressure in the vacuum chamber is adjusted to 30-50 Pa, and a direct current pulse power is applied to the workpiece electrode and the auxiliary electrode to perform glow discharge nitriding treatment, the treatment temperature is 450-500°C, the treatment time is 4-24 h, and the workpiece is cooled in the furnace after the treatment.

[0025] Further, the flow ratio of N2 to Ar is 1:4-1:3.

[0026] The workpiece after the nitriding treatment is polished to remove the loose layer on the surface and reduce the surface roughness, and a final titanium alloy bar with high fatigue performance is obtained.

[0027] In the above technical solution, (1) a composite surface modification layer is formed on the surface of the titanium alloy base body through surface alloying (TiCuAl coating) and low-temperature ion nitriding process. The TiCuAl coating serves as an intermediate layer. Nitrogen atoms will preferentially react with Ti. A large number of Cu phases will exist in the form of soft islands, can absorb stress, inhibit crack propagation, and form short-circuit diffusion paths inside the coating. The diffusion rate of nitrogen atoms along these paths is much higher than that in the titanium alloy base body, which reduces the energy barrier required for the formation of Ti-N bonds. This allows nitrogen atoms to be absorbed and combined with Ti at a low temperature of 400-500 DEG C to form a large number of fine nitride (such as TiN, Ti2N) particles. The activity of Al is higher than that of Ti, and Al has a strong affinity with N, which can preferentially react with N to form fine AlN particles. These particles act as heterogeneous nucleation points, refine TiN grains, and create more grain boundaries and defects to provide short-circuit paths for further diffusion of nitrogen, and play a catalytic role. At the same time, these AlN particles play a role in strong dispersion strengthening and grain refinement in the infiltration layer. The plastic deformation ability of the Cu phase can coordinate and release the internal stress generated by the formation of nitrides and the thermal stress between the coating and the base body, effectively inhibiting the generation of microcracks, which is the key to obtaining high bonding strength and high fatigue performance.

[0028] Finally, a composite strengthening layer is formed, which has high surface hardness and is filled with hard TiN, Ti2N and AlN as the skeleton to bear the load, and soft Cu phase to wrap these particles, which greatly improves the wear resistance of the material. Through plastic deformation to absorb energy and passivate crack tips, the toughness is improved.

[0029] (2) Ti and Al have good compatibility with the titanium alloy base body. At the nitriding temperature, more moderate interdiffusion will occur at the interface between the coating and the base body, forming a firm metallurgical bond. The volume expansion caused by nitriding generates compressive stress at the interface, which helps to improve the bonding strength, which is the basis for improving the fatigue performance.

[0030] (3) During the nitriding process, the penetration of nitrogen atoms and the formation of new phases (TiN, AlN) will cause volume expansion, which is constrained by the base body, thereby forming a residual compressive stress layer on the surface of the material. The compressive stress layer can effectively offset the tensile stress generated by external load, greatly inhibit the initiation of fatigue cracks, and thus improve the fatigue resistance of the titanium alloy bar.

[0031] The low-temperature nitriding process (<500℃) ensures that the microstructure of the titanium alloy substrate does not change, avoids grain coarsening and phase transformation brittleness caused by overheating, and enables the core strength and toughness matching to be retained. The final rod not only has outstanding fatigue performance, but also has synchronous enhancement of surface hardness, wear resistance and corrosion resistance, fully utilizes the advantages of surface modification technology, and stably prepares titanium alloy rods with high fatigue performance, which can meet the harsh requirements of high-end equipment key components on comprehensive performance of materials.

[0032] The Ni element in the TiNiAl coating creates a large number of fast channels for nitrogen atom diffusion and catalyzes the nitriding reaction at low temperature, realizing low-temperature deep nitriding. After long-time nitriding, a diffusion layer with considerable thickness and smooth hardness transition is formed. The layer is firmly combined with the substrate, avoiding performance mutation. The high-hardness nitride layer on the surface and the diffusion layer below can effectively inhibit the initiation of fatigue cracks. More importantly, the nitriding process and subsequent polishing introduce a large amount of residual compressive stress on the surface, which can greatly offset the tensile stress generated by external alternating loads, thereby greatly improving the fatigue limit and fatigue life. The low-temperature nitriding process ensures that the microstructure and strength-toughness matching of the titanium alloy substrate itself do not deteriorate. Replacing Cu with Ni can optimize the fast channel for nitrogen atom diffusion, catalyze the low-temperature nitriding process, increase the thickness of the nitriding layer, and improve the layer toughness and bonding force.

[0033] Further, the alloy target material also contains 0.5% to 2% of rare earth elements, and the rare earth elements are one of yttrium (Y) and cerium (Ce). The introduction of rare earth elements can refine the grains of the coating and the nitriding layer, promote the diffusion of nitrogen elements, increase the nitriding rate and layer depth, and enhance the coating toughness and bonding force.

[0034] Further, in the alloy target material, silicon (Si) is used to partially replace Ni or Cu; The replacement amount is 1-5% of Ni or Cu. The introduction of silicon elements can significantly improve the high-temperature oxidation resistance and hardness of the rod, and has better oxidation resistance, tempering softening resistance and thermal fatigue performance at higher temperatures (such as 500-600℃).

[0035] Further, in the low-temperature ion nitriding process, methane is also introduced, and the flow ratio of N2 to CH4 is 1:10 to 1:5.

[0036] Methane in low temperature ion nitriding, with active nitrogen atom together into the coating and surface layer of the substrate, can form Ti (CN) and other carbonitride. The phase compared with pure TiN or Ti2N has lower friction coefficient and better toughness, can effectively inhibit the initiation of fatigue crack. C and N co-diffusion can produce more significant solid solution strengthening and precipitation strengthening effect, make the hardness gradient of the layer more gentle, reduce stress concentration, benefit to the improvement of fatigue performance. The introduction of carbon can refine the nitride grain, make the layer more dense and uniform.

[0037] Further, the alloy target material is subjected to surface treatment, and the specific process is as follows: the alloy target material is put into boronizing agent and kept at 950-1050 DEG C for 10-30 hours; then, the target material is subjected to alkali washing, grinding and polishing.

[0038] Further, the boronizing agent comprises the following components in mass: 50-70 parts of borax, 15-25 parts of aluminum powder, 10-20 parts of boron powder and 3-8 parts of cerium dioxide.

[0039] A layer of extremely hard TiB2permeation layer is formed on the surface of the target material, the hardness, wear resistance and arc ablation resistance of the surface of the target material are significantly improved, the generation of micro-particles in the sputtering process is reduced, and thus a more dense and less defective coating is obtained. Trace boron (B) elements are sputtered and fused into the coating. B is a strong grain strengthening agent, can further refine the coating grains, and can form extremely hard BN phase in subsequent nitriding, which has a positive effect on improving the surface hardness and wear resistance.

[0040] Compared with the prior art, the present application has the following advantages: The present application forms a composite surface modification layer on the surface of the titanium alloy substrate through surface TiAl alloying and low temperature ion nitriding. Cu, Ni and Al help to refine the nitride grains and provide sufficient Ti elements for subsequent nitriding, so that a nitriding layer with high hardness and high wear resistance is formed, and residual compressive stress is introduced on the surface, thereby significantly improving the fatigue resistance of the titanium alloy rod and maintaining the microstructure and performance characteristics of the titanium alloy substrate. DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are only some of the embodiments of the present application, but not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work fall within the scope of the present application.

[0042] In the following detailed description, the "parts" and "%" are mass parts or mass percentages, unless otherwise specified. In Examples 1-7 and Comparative Examples 1-3, the titanium alloy substrate was prepared by mixing sponge titanium and alloying elements, melting, and casting into ingots; and then sequentially subjected to forging, rolling, heat treatment, machining, surface treatment, nondestructive testing and physicochemical testing; the melting was performed by vacuum arc remelting, low-current starting arc, first melting at a current of 9000 A, second VAR melting at 11000 A, and third melting at 13500 A, with a vacuum degree < 5 x 10 -2 forging: open forging at a temperature of 1100℃, deformation of 30% per heating, total deformation of 66%, and a final forging temperature of 955℃; intermediate forging at a temperature of 920℃, deformation of 40% per heating, total deformation of 64%, and a final forging temperature of 855℃; finish forging at a temperature of 810℃, deformation of 22% per heating, total deformation of 53%, and a final forging temperature of 785℃, air cooling; rolling process at a heating temperature of 820℃, a final rolling temperature of 810℃, deformation of 15% per pass, total deformation of 80%, and a final rolling temperature of 785℃, air cooling; heat treatment by solid solution + aging, solid solution treatment at a temperature of 880℃ for 1h, water quenching; aging treatment at a temperature of 540℃ for 6h, air cooling; surface treatment including pickling and sandblasting / shot blasting, pickling using a 45℃ HF-HNO3 mixed acid solution (HF:HNO3:H2O volume ratio of 1:3:8) for 10min; sandblasting using 100-150 mesh glass beads at a pressure of 0.4MPa; shot blasting strength of 0.20mmA, coverage of 120%, and shot of cast glass shot; the titanium alloy substrate comprises the following components: aluminum: 4.7%, molybdenum: 4.3%, vanadium: 5.1%, chromium: 3.5%, zirconium: 4.0%, palladium: 0.7%, iron: 0.05%, carbon: 0.013%, nitrogen: 0.010%, oxygen: 0.020%, and hydrogen: 0.0012%, by mass percentage; the balance being titanium; and cleaning and surface activation treatment were performed to remove the oxide layer and contaminants; borax (Na2B4O7): purity > 99%; aluminum powder: Al > 99.9%; boron powder: amorphous boron powder, B > 95%; cerium dioxide: CeO2 > 99%; Target size: Φ50mm x 3mm.

[0043] Example 1: A method for preparing a titanium alloy rod with high fatigue performance, comprising the following processes: Step 1, depositing a TiCuAl alloy coating: Take titanium alloy rod as the base, and deposit a TiCuAl alloy coating with a thickness of 1 μm on the surface of the titanium alloy rod; the TiCuAl alloy coating is obtained by direct current magnetron sputtering deposition, and the process parameters of the magnetron sputtering are as follows: a power of 80 W, an operating air pressure of 0.4 Pa, a target-to-substrate distance of 120 mm, and a substrate table rotation speed of 20 rpm; the TiCuAl alloy target material comprises the following components: Ti: 60% by mass, Cu: 30% by mass, and Al: 10% by mass; Step 2, low-temperature ion nitriding: The titanium alloy on which the TiCuAl alloy coating is deposited is placed in a vacuum chamber of an ion nitriding furnace, and after vacuumizing, a mixed gas of nitrogen and argon is introduced, the flow ratio of N2 to Ar is 1:4, the air pressure in the vacuum chamber is adjusted to 30 Pa, and glow discharge nitriding treatment is performed by applying a direct current pulse power source to the workpiece electrode and the auxiliary electrode, the treatment temperature is 450℃, and the treatment time is 24 hours; after the treatment, the workpiece is cooled in the furnace, polished, a nitriding layer is formed, and a titanium alloy rod with high fatigue performance is obtained.

[0044] Example 2: A method for preparing a titanium alloy rod with high fatigue performance, comprising the following processes: Step 1, depositing a TiCuAl alloy coating: Take titanium alloy rod as the base, and deposit a TiCuAl alloy coating with a thickness of 2 μm on the surface of the titanium alloy rod; the TiCuAl alloy coating is obtained by direct current magnetron sputtering deposition, and the process parameters of the magnetron sputtering are as follows: a power of 100 W, an operating air pressure of 0.6 Pa, a target-to-substrate distance of 110 mm, and a substrate table rotation speed of 15 rpm; the TiCuAl alloy target material comprises the following components: Ti: 65% by mass, Cu: 22% by mass, Al: 10% by mass, Si: 2% by mass, and Y: 1% by mass; Step 2, low-temperature ion nitriding: The titanium alloy on which the TiCuAl alloy coating is deposited is placed in a vacuum chamber of an ion nitriding furnace, and after vacuumizing, a mixed gas of nitrogen and argon is introduced, the flow ratio of N2 to Ar is 1:3.5, the air pressure in the vacuum chamber is adjusted to 40 Pa, and glow discharge nitriding treatment is performed by applying a direct current pulse power source to the workpiece electrode and the auxiliary electrode, the treatment temperature is 480℃, and the treatment time is 18 hours; after the treatment, the workpiece is cooled in the furnace, polished, a nitriding layer is formed, and a titanium alloy rod with high fatigue performance is obtained.

[0045] Example 3: A method for preparing a titanium alloy rod with high fatigue performance, comprising the following processes: Step 1, depositing a TiCuAl alloy coating: Take titanium alloy rod as the base, and deposit a TiCuAl alloy coating with a thickness of 3 μm on the surface of the titanium alloy rod; The TiCuAl alloy coating is obtained by direct current magnetron sputtering deposition, and the process parameters of magnetron sputtering are as follows: power 120 W, working pressure 0.8 Pa, target-substrate distance 100 mm, and base table rotation speed 10 rpm; the TiCuAl alloy target material comprises the following components: Ti 70%, Cu 20%, Al 8%, and Y 2% by mass percentage; Step 2, low-temperature ion nitriding: The titanium alloy on which the TiCuAl alloy coating is deposited is placed in a vacuum chamber of an ion nitriding furnace, and after vacuumizing, a mixed gas of nitrogen and argon is introduced, the flow ratio of N2 to Ar being 1:3, the gas pressure in the vacuum chamber is adjusted to 50 Pa, and glow discharge nitriding treatment is performed by applying a direct current pulse power source to the workpiece electrode and the auxiliary electrode, the treatment temperature being 500 DEG C and the treatment time being 12 h; after the treatment, the workpiece is cooled in the furnace, polished, and a nitriding layer is formed, thereby obtaining a titanium alloy rod with high fatigue performance.

[0046] Example 4: a method for preparing a titanium alloy rod with high fatigue performance, comprising the following processes: Step 1, depositing a TiNiAl alloy coating: A titanium alloy rod is taken as a substrate, and a TiNiAl alloy coating with a thickness of 3 μm is deposited on the surface of the substrate; the TiNiAl alloy coating is obtained by direct current magnetron sputtering deposition, and the process parameters of magnetron sputtering are as follows: power 120 W, working pressure 0.8 Pa, target-substrate distance 100 mm, and base table rotation speed 10 rpm; the TiNiAl alloy target material comprises the following components: Ti 70%, Ni 20%, Al 8%, and Y 2% by mass percentage. Step 2, low-temperature ion nitriding: The titanium alloy on which the TiNiAl alloy coating is deposited is placed in a vacuum chamber of an ion nitriding furnace, and after vacuumizing, a mixed gas of nitrogen and argon is introduced, the flow ratio of N2 to Ar being 1:4, the gas pressure in the vacuum chamber is adjusted to 30 Pa, and glow discharge nitriding treatment is performed by applying a direct current pulse power source to the workpiece electrode and the auxiliary electrode, the treatment temperature being 450 DEG C and the treatment time being 24 h; after the treatment, the workpiece is cooled in the furnace, polished, and a nitriding layer is formed, thereby obtaining a titanium alloy rod with high fatigue performance.

[0047] Example 5: a method for preparing a titanium alloy rod with high fatigue performance, comprising the following processes: Step 1, depositing a TiNiAl alloy coating: The TiNiAl alloy target material is placed in a boronizing agent and is kept at 950 DEG C for 30 h; then, the TiNiAl alloy target material is subjected to alkaline washing, grinding, and polishing; the TiNiAl alloy target material comprises the following components: Ti 70%, Ni 20%, Al 8%, and Y 2% by mass percentage; the boronizing agent comprises the following mass components: 50 parts of borax, 15 parts of aluminum powder, 10 parts of boron powder, and 3 parts of cerium dioxide; Take titanium alloy rod as the base, deposit TiNiAl alloy coating with a thickness of 3 μm on its surface; the TiNiAl alloy coating is obtained by direct current magnetron sputtering deposition, the power is 120 W, the working air pressure is 0.8 Pa, the target-substrate distance is 100 mm, and the base table rotation speed is 10 rpm; Step 2, low-temperature ion nitriding: The titanium alloy on which the TiNiAl alloy coating is deposited is placed in the vacuum chamber of the ion nitriding furnace, after vacuumizing, a mixed gas of nitrogen and argon is introduced, the flow ratio of N2 to Ar is 1:4, the air pressure in the vacuum chamber is adjusted to 30 Pa, a direct current pulse power is applied to the workpiece electrode and the auxiliary electrode to carry out glow discharge nitriding treatment, the treatment temperature is 450℃, and the time is 24 h; after the treatment, the workpiece is cooled in the furnace, polished, a nitriding layer is formed, and a titanium alloy rod with high fatigue performance is obtained.

[0048] Example 6: A preparation method of a titanium alloy rod with high fatigue performance, comprising the following processes: Step 1, depositing TiNiAl alloy coating: The TiNiAl alloy target material is placed in a boronizing agent and is kept at 1000℃ for 20 h; then it is washed with alkali, polished, and polished; the TiNiAl alloy target material comprises the following components: Ti: 70%, Ni: 20%, Al: 8%, and Y: 2% by mass percentage; the boronizing agent comprises the following mass components: 60 parts of borax, 20 parts of aluminum powder, 15 parts of boron powder, and 5 parts of cerium dioxide; Take titanium alloy rod as the base, deposit TiNiAl alloy coating with a thickness of 3 μm on its surface; the TiNiAl alloy coating is obtained by direct current magnetron sputtering deposition, the power is 120 W, the working air pressure is 0.8 Pa, the target-substrate distance is 100 mm, and the base table rotation speed is 10 rpm; Step 2, low-temperature ion nitriding: The titanium alloy on which the TiNiAl alloy coating is deposited is placed in the vacuum chamber of the ion nitriding furnace, after vacuumizing, a mixed gas of nitrogen, methane and argon is introduced, the flow ratio of N2 to Ar is 1:4, the flow ratio of methane to N2 is 1:10, the air pressure in the vacuum chamber is adjusted to 30 Pa, a direct current pulse power is applied to the workpiece electrode and the auxiliary electrode to carry out glow discharge nitriding treatment, the treatment temperature is 450℃, and the time is 24 h; after the treatment, the workpiece is cooled in the furnace, polished, a nitriding layer is formed, and a titanium alloy rod with high fatigue performance is obtained.

[0049] Example 7: A preparation method of a titanium alloy rod with high fatigue performance, comprising the following processes: Step 1, depositing TiNiAl alloy coating: Put the TiNiAl alloy target into the boronizing agent, heat preservation at 1050℃ for 10h; then alkaline washing, polishing, polishing; the TiNiAl alloy target comprises the following components: Ti: 70%, Ni: 20%, Al: 8%, Y: 2% by mass percentage; the boronizing agent comprises the following mass components: 70 parts of borax, 25 parts of aluminum powder, 20 parts of boron powder, 8 parts of cerium dioxide; Take titanium alloy bar as the substrate, and deposit a TiNiAl alloy coating with a thickness of 3μm on the surface of the titanium alloy bar; the TiNiAl alloy coating is obtained by direct current magnetron sputtering deposition, and the process parameters of the magnetron sputtering are as follows: power 120W, working pressure 0.8Pa, target-substrate distance 100mm, and substrate rotation speed 10rpm; Step 2, low-temperature ion nitriding: Put the titanium alloy on which the TiNiAl alloy coating is deposited into the ion nitriding furnace vacuum chamber, and after vacuumizing, introduce a mixed gas of nitrogen, methane and argon, the flow ratio of N2 to Ar is 1:4, the flow ratio of methane to N2 is 1:5, the gas pressure in the vacuum chamber is adjusted to 30Pa, glow discharge nitriding treatment is carried out by applying direct current pulse power on the workpiece electrode and the auxiliary electrode, the treatment temperature is 450℃, and the treatment time is 24h; after the treatment, the workpiece is cooled in the furnace, polished, a nitriding layer is formed, and a titanium alloy bar with high fatigue performance is obtained.

[0050] Comparative Example 1: a preparation method of a titanium alloy bar with high fatigue performance, comprising the following processes: Step 1, depositing a TiAl alloy coating: Take titanium alloy bar as the substrate, and deposit a TiAl alloy coating with a thickness of 1μm on the surface of the titanium alloy bar; the TiAl alloy coating is obtained by direct current magnetron sputtering deposition, and the process parameters of the magnetron sputtering are as follows: power 80W, working pressure 0.4Pa, target-substrate distance 120mm, and substrate rotation speed 20rpm; the TiAl alloy target comprises the following components: Ti: 85%, Al: 15% by mass percentage; Step 2, low-temperature ion nitriding: Put the titanium alloy on which the TiAl alloy coating is deposited into the ion nitriding furnace vacuum chamber, and after vacuumizing, introduce a mixed gas of nitrogen and argon, the flow ratio of N2 to Ar is 1:4, the gas pressure in the vacuum chamber is adjusted to 30Pa, glow discharge nitriding treatment is carried out by applying direct current pulse power on the workpiece electrode and the auxiliary electrode, the treatment temperature is 450℃, and the treatment time is 24h; after the treatment, the workpiece is cooled in the furnace, polished, a nitriding layer is formed, and a titanium alloy bar with high fatigue performance is obtained.

[0051] Comparative Example 2: a preparation method of a titanium alloy bar with high fatigue performance, comprising the following processes: The titanium alloy on which the TiAl alloy coating is deposited is placed in the vacuum chamber of an ion nitriding furnace, after vacuumizing, mixed gas of nitrogen and argon is introduced, the flow ratio of N2 to Ar is 1:4, the gas pressure in the vacuum chamber is adjusted to 30 Pa, glow discharge nitriding treatment is carried out by applying direct current pulse power on the workpiece electrode and the auxiliary electrode, the treatment temperature is 450℃, and the treatment time is 24 hours; after treatment, the workpiece is cooled in the furnace, polished, a nitriding layer is formed, and a titanium alloy rod with high fatigue performance is obtained.

[0052] Comparative Example 3: A method for preparing a titanium alloy rod with high fatigue performance, comprising the following processes: The titanium alloy on which the TiAl alloy coating is deposited is placed in the vacuum chamber of an ion nitriding furnace, after vacuumizing, mixed gas of nitrogen and argon is introduced, the flow ratio of N2 to Ar is 1:4, the gas pressure in the vacuum chamber is adjusted to 30 Pa, glow discharge nitriding treatment is carried out by applying direct current pulse power on the workpiece electrode and the auxiliary electrode, the treatment temperature is 650℃, and the treatment time is 24 hours; after treatment, the workpiece is cooled in the furnace, polished, a nitriding layer is formed, and a titanium alloy rod with high fatigue performance is obtained.

[0053] Comparative Example 4: The titanium alloy substrate comprises the following components: iron: 0.040%, carbon: 0.021%, nitrogen: 0.023%, oxygen: 0.104%, hydrogen: 0.0014%, and the balance is titanium.

[0054] Experiment: Take the titanium alloy substrate and titanium alloy rod obtained in Examples 1-7 and Comparative Examples 1-4 to prepare test samples, and detect the performance of the test samples respectively and record the detection results: The room temperature tensile properties of the titanium alloy substrate test sample are detected with GB / T228.1-2010 as the reference standard; Fatigue resistance test: The high cycle fatigue properties of the test sample are detected by a servo hydraulic fatigue testing machine with ASTM E466 / ISO 1099 as the reference standard, and the fatigue limit at 10^7 cycles is recorded; Surface micro Vickers hardness test: The surface hardness (HV0.05) of the test sample is detected by a micro Vickers hardness tester with ASTM E384 / ISO 6507 as the reference standard; Wear resistance test: The wear volume of the test sample is detected by a ball-on-disc friction and wear testing machine with Si3N4 as the grinding ball to characterize the wear resistance with ASTM G99 as the reference standard; Corrosion resistance test: The self-corrosion potential of the test sample is detected by electrochemical test in 3.5wt% NaCl solution to characterize the corrosion resistance with ASTM G61 as the reference standard; Surface layer bonding strength test: The critical load of complete peeling of the test sample is detected by a scratch testing machine with a diamond indenter with ASTM C1624 as the reference standard.

[0055] Table 1, performance experimental data of titanium alloy base body

[0056] Table 2, performance experimental data of titanium alloy rod

[0057] According to the data in the above table, the following conclusions can be clearly obtained: The titanium alloy rod obtained in Examples 1-7 is compared with the titanium alloy rod obtained in Comparative Examples 1-3, and the test results show that, Compared with the titanium alloy base body in the comparative example, the titanium alloy rod obtained in Examples 1-7 has higher fatigue limit, surface hardness, critical load, self-corrosion potential data, and lower wear volume data. This fully illustrates that the present application improves the fatigue resistance of the prepared titanium alloy rod, and simultaneously improves the hardness, wear resistance and corrosion resistance, and the surface layer formed by alloying + nitriding has good bonding strength.

[0058] Compared with Example 1, silicon and yttrium are added to the alloy target material in Examples 2 and 3, so that the hardness and wear resistance, corrosion resistance are improved, and the bonding force is also improved.

[0059] Compared with Example 4, the alloy target material in Example 5 is a boronizing target material, and after magnetron sputtering, the alloy coating formed has higher quality, and the surface layer after nitriding is more dense, and the hardness, wear resistance and corrosion resistance are improved.

[0060] In the ion nitriding process of Example 6 and Example 7, CH4 is introduced, and TiCN phase is formed by carbonitriding, which has higher hardness and wear resistance; at the same time, the introduction of carbon makes the penetration layer more ductile, and the critical load (bonding force) is higher.

[0061] The alloy coating in Comparative Example 1 is TiAl coating, and no element Cu or Ni is set, and its performance is not as good as TiCuAl and TiNiAl series, and the data performance is reduced.

[0062] Comparative Example 2 directly nitrides the titanium alloy rod without setting a coating auxiliary, and the penetration layer is thin and has limited performance, and the wear resistance and corrosion resistance are improved by a small margin.

[0063] In Comparative Example 3, the surface treatment process of the titanium alloy is high-temperature nitriding, and high temperature seriously damages the titanium alloy base body, the core hardness decreases, and the overall fatigue performance deteriorates; the penetration layer is deep but loose, and the wear resistance and corrosion resistance are significantly reduced due to the deterioration of the surface state.

[0064] The titanium alloy substrate of Comparative Example 4 does not contain alloying elements, and after performance testing, it is found that the mechanical properties, corrosion resistance, fatigue resistance, surface hardness and wear resistance are all worse than those of the titanium alloy substrate of Example 1. It can be seen that the alloying of the titanium alloy substrate helps to improve its various properties.

[0065] It will be obvious to a person skilled in the art that, without departing from the scope of the present application, the application can be implemented in other specific forms. Therefore, the examples should be considered in all respects as illustrative and not restrictive, the scope of the application being defined by the appended claims rather than by the description given above, and it is therefore intended that all changes which come within the meaning and range of equivalency of the claims are resolutely encompassed by the application.

Claims

1. A method for preparing high-fatigue-performance titanium alloy bars, characterized in that: Including the following processes: A titanium alloy rod is used as the substrate, and a TiAl alloy coating is deposited on its surface. Then, low-temperature ion nitriding is performed to form a nitrided layer, resulting in high-fatigue-performance titanium alloy bars. The alloy target used in the preparation of TiAl alloy coating is a TiAl alloy target, a TiCuAl alloy target, or a TiNiAl alloy target; The alloy target material undergoes boronizing surface treatment.

2. The method for preparing a high-fatigue-performance titanium alloy bar according to claim 1, characterized in that: The TiAl alloy coating is obtained by deposition of an alloy target using DC magnetron sputtering.

3. The method for preparing a high-fatigue-performance titanium alloy bar according to claim 1, characterized in that: The low-temperature ion nitriding process is as follows: Titanium alloys with TiAl alloy coatings are placed in the vacuum chamber of an ion nitriding furnace. After evacuation, a mixture of nitrogen and argon is introduced. The pressure in the vacuum chamber is adjusted to 30–50 Pa. A DC pulse power supply is applied to the workpiece electrode and the auxiliary electrode to perform glow discharge nitriding treatment. The treatment temperature is 450–500 °C and the time is 4–24 h. The furnace is then cooled after treatment.

4. The method for preparing a high-fatigue-performance titanium alloy bar according to claim 2, characterized in that: The alloy target material also contains 0.5% to 2% rare earth elements, one of which is yttrium or cerium.

5. The method for preparing a high-fatigue-performance titanium alloy bar according to claim 1, characterized in that: The boronizing surface treatment process of the alloy target is as follows: the alloy target is placed in a boronizing agent and kept at 950-1050℃ for 10-30 hours.

6. The method for preparing a high-fatigue-performance titanium alloy bar according to claim 5, characterized in that: The boronizing agent comprises the following components by weight: 50-70 parts borax, 15-25 parts aluminum powder, 10-20 parts boron powder, and 3-8 parts cerium dioxide.

7. The method for preparing a high-fatigue-performance titanium alloy bar according to claim 1, characterized in that: The titanium alloy matrix comprises the following components by mass percentage: aluminum: 4.5–5.5%, molybdenum: 4.0–5.0%, vanadium: 4.5–5.5%, chromium: 3.0–4.0%, zirconium: 3.5–4.5%, iron: ≤0.25%, oxygen: ≤0.10%, tantalum or palladium: 0.5–1.0%, hydrogen: <50 ppm; the balance being titanium.

8. The method for preparing a high-fatigue-performance titanium alloy bar according to claim 2, characterized in that: In the alloy target material, silicon is used to replace 1-5% of Ni or Cu.

9. The method for preparing a high-fatigue-performance titanium alloy bar according to claim 3, characterized in that: The flow rate ratio of nitrogen to argon is 1:4 to 1:

3.

10. A high-fatigue-performance titanium alloy bar prepared by the preparation method according to any one of claims 1-9.

Citation Information

Patent Citations

  • Process for preparing (Ti,Al)BN ceramic amorphous-nanocrystalline wear-resistant anti-corrosion composite coating

    CN102660732A

  • Vacuum medium-frequency induction smelting metal purification method for titanium-nickel alloy

    CN106148884A

  • Method for improving high toughness of titanium aluminum nitrogen coating on surface of hard alloy

    CN109338319A

  • Method for preparing antifriction anti-fretting strengthening layer on surface of titanium alloy

    CN109837549A

  • TiAl coating capable of improving high-temperature oxidation resistance of titanium alloy and preparation method of TiAl coating

    CN113652644A